PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PEREDARAN MIE BASAH YANG MENGANDUNG ZAT BERBAHAYA OLEH PELAKU USAHA DI KOTA PEKANBARU - Fernanda, Rian Dwiky; ', Firdaus; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The more advanced and growing community or consumers in Indonesia,the more consumer demands will be things practical. In eraglobal the easier thecirculation of food products from within and abroad that enter the domesticmarket so as to avoid the possibility of expired food products, and containing orcontaminated with hazardous substances and prohibited food additives such asformalin, borax, rodhamin B, methanyl yellow or processed food originating fromthe import of substandard waste food.As for the purpose of writing this thesis is To know the Legal Protectionfor Consumers Against Circulation of Wet Noodles Containing DangerousSubstance By Business Executors In Pekanbaru City, as well as obstacles.The conclusion that can be obtained from this research is, First, theprotection of the law for consumers to the circulation of wet noodles containingharmful substances by business actors in the city of Pekanbaru is still not runningproperly, where there are still many consumers who are harmed due to thecirculation of wet noodles containing hazardous substances, Second, barriers inlegal protection for consumers to the circulation of wet noodles containinghazardous substances by business actors in Pekanbaru city caused by severalfactors including, consumer factors, business actors, and government. Suggestionwriter in this research is, First, Government should increase supervision tocirculation of wet noodle containing hazardous materials in Pekanbaru City tominimize losses suffered by society Second, business actors in running theirbusiness should show good faith and give clear information of goods and orservices circulated and attempts to pay attention to consumer rights andobligations as business actors that have been formulated in the UUPK and alsoconsumers wet noodles should be more careful in buying and consuming wetnoodles to avoid danger.Keywords: Legal Conservation - Consumer - Wet Noodle - DangerousSubstance - Business Actor